Analysis of Appraisal System in News Text â€œBerebut Vaksinâ€: A Study of Systemic Functional of Linguistic - Andi Indah Yulianti; Dwiani Septiana; Darmawati Majid Rosni (Jurusan Tadris Bahasa Indonesia, 2021)
This study aims to describe the type, form, influence, and reasons for the attitude used in the news text. This qualitative descriptive research data comes from the news text on medcom.id entitled